Discovery of Inhibitors of Trypanosoma brucei by Phenotypic Screening of a Focused Protein Kinase Library. Issue 11 (18th September 2015) - Woodland, Andrew; Thompson, Stephen; Cleghorn, Laura A. T.; Norcross, Neil; De Rycker, Manu; Grimaldi, Raffaella; Hallyburton, Irene; Rao, Bhavya; Norval, Suzanne; Stojanovski, Laste; Brun, Reto; Kaiser, Marcel; et al.
Abstract: A screen of a focused kinase inhibitor library against Trypanosoma brucei rhodesiense led to the identification of seven series, totaling 121 compounds, which showed >50 % inhibition at 5 μm . Screening of these hits in a T. b. brucei proliferation assay highlighted three compounds with a 1 H ‐imidazo[4, 5‐ b ]pyrazin‐2(3 H )‐one scaffold that showed sub‐micromolar activity and excellent selectivity against the MRC5 cell line. Subsequent rounds of optimisation led to the identification of compounds that exhibited good in vitro drug metabolism and pharmacokinetics (DMPK) properties, although in general this series suffered from poor solubility. A scaffold‐hopping exercise led to the identification of a 1 H ‐pyrazolo[3, 4‐ b ]pyridine scaffold, which retained potency. A number of examples were assessed in a T. b. brucei growth assay, which could differentiate static and cidal action. Compounds from the 1 H ‐imidazo[4, 5‐ b ]pyrazin‐2(3 H )‐one series were found to be either static or growth‐slowing and not cidal. Compounds with the 1 H ‐pyrazolo[3, 4‐ b ]pyridine scaffold were found to be cidal and showed an unusual biphasic nature in this assay, suggesting they act by at least two mechanisms. Abstract : Focused on tipping the HAT : We report a phenotypic screen of a focused kinase library against Trypanosoma brucei and subsequent optimisation of a hit, with sub‐micromolar activity, based on a 1 H ‐imidazo[4, 5‐ b ]pyrazin‐2(3 H )‐one scaffold. Scaffold hopping gave a second series based on a 1 H ‐pyrazolo[3, 4‐ b ]pyridine scaffold, also with sub‐micromolar activity. The first series of compounds were static or growth‐slowing and not cidal, whilst those from the second series were cidal, but showed an unusual biphasic growth curve, suggestive of several mechanisms of action.